Simple support binder relationship with mother's confidence when caring for BBLR at the Sei Berombang Health Center - Paninsari, Debora; Sarumaha, Jensari Ariani; Harefa, Jessica Margareth; Samosir, Julianti; Khairani, Khairani; Rijsubo, Primawty Dwi; Pane, Yulia Hanim (Priviet Social Sciences Journal, 2023)
BBLR babies are babies born with abnormal birth weight (up to 2,499 g) (Sarwono, 2006: 376). Based on the mortality and morbidity rate, low birth weight babies are still a problem from a global or national perspective. To find out the relationship between simple support binder and mother's confidence when caring for BBLR at the Sei Berombang Health Center, Kec. Panai Hilir, Kel. Sei Berombang, Kab. Labuhan Batu, it is necessary to do the kangaroo method treatment with a simple support binder to find out the addition of BBLR babies. The type of research is quasi-experimental research in one group (one group pre test post test design). Sampling using total sampling technique using a questionnaire instrument. The sample is 30 respondents. Data analysis will be carried out using univariate analysis and bivariate analysis. Data collection was carried out using the Wilcoxon test with a degree of significance (α=0.05). Based on the results of the Wilcoxon statistical test (p-value = 0.000) then Ha is accepted and Ho is rejected, meaning that there is a simple support binder relationship with the mother's confidence when caring for BBLR. And there was an increase in the baby's weight after the kangaroo method was applied with a simple support binder. In this case the mother is more confident in caring for the kangaroo method with a simple support binder.